The impact of electronic cigarette on mental health among adolescents and young adults: a systematic review - Nurannisa, Nurannisa; Luthfiatun Ulinnuha, Lu’lu; Syed Elias, Sharifah Munirah (IIUM Press, 2026)
Background: The use of electronic cigarettes (e-cigarettes) has risen significantly among adolescents and young adults globally. While the physical health risks are increasingly documented, the impact of vaping on mental health in this demographic requires further synthesis of the available evidence. This literature review aims to consolidate scientific evidence about the impact of ecigarette use on the mental health of adolescents and young adults. Methods: A systematic literature review was conducted following the PRISMA protocol. Searches were performed in Scopus, PubMed, ProQuest, and Cochrane databases for publications from 2021 to 2025. The search strategy used keywords related to electronic cigarette, mental health, and young populations. After screening, 23 articles met the inclusion criteria for full-text analysis. Results: E-cigarette use and mental health were found to be significantly correlated negatively in the great majority of the previous studies. The most consistently identified impacts included increased symptoms of depression, anxiety, and psychological stress. Furthermore, e-cigarette was associated with more severe outcomes, including non-suicidal self-injury, suicidal ideation, poor sleep quality, and psychological distress. Longitudinal studies indicated that persistent e-cigarette could predict the future onset of depressive symptoms. These findings were consistent across diverse geographical and cultural contexts. Conclusion: E-cigarette use is associated with a range of adverse mental health outcomes among adolescents and young adults, from common disorders like depression and anxiety to severe risks such as suicidality. These findings point out the need for targeted public health interventions and international strategies to address the mental health risks of e-cigarette in younger populations.